Complex RNA Secondary Structures Mediate Mutually Exclusive Splicing of Coleoptera Dscam1 - Dong, Haiyang; Li, Lei; Zhu, Xiaohua; Shi, Jilong; Fu, Ying; Zhang, Shixin; Shi, Yang; Xu, Bingbing; Zhang, Jian; Shi, Feng; Jin, Yongfeng (Frontiers in Genetics, 2021)
Mutually exclusive splicing is an important mechanism for expanding protein diversity. An extreme example is the Down syndrome cell adhesion molecular (Dscam1) gene of insects, containing four clusters of variable exons ( exon 4, 6, 9, and 17) which potentially generates tens of thousands of protein isoforms through mutually exclusive splicing, of which regulatory mechanisms are still elusive. Here, we systematically analyzed the variable exon 4, 6, and 9 clusters of Dscam1 in Coleoptera species. Through comparative genomics and RNA secondary structure prediction, we found apparent evidence that the evolutionarily conserved RNA base-pairing mediates mutually exclusive splicing in the Dscam1 exon 4 cluster. In contrast to the fly exon 6, most exon 6 selector sequences in Coleoptera species are partially located in the variable exon region. Besides, bidirectional RNA-RNA interactions are predicted to regulate the mutually exclusive splicing of variable exon 9 of Dscam1. Although the docking sites in exon 4 and 9 clusters show clade-specific, the docking sites-selector base-pairing is conserved in secondary structure level. In short, our result provided a mechanistic framework that the application of long-range RNA base-pairings in regulating the mutually exclusive splicing of Coleoptera Dscam1.